KUALITAS KREDIT SEBAGAI PEMODERASI PENGARUH TINGKAT PENYALURAN KREDIT DAN DANA PIHAK KETIGA PADA PROFITABILITAS - Trisna Dewi, Anak Agung Ayu; Budiartha, I Ketut (E-Jurnal Akuntansi, 2017)
Profitability is the ability of the company makes a profit by utilizing all its assets and capital. This study aims to determine the effect of loan portfolio and third party fund in profitability and credit quality as a moderating. This study was conducted in 35 LPD Denpasar with the observation period 2013-2015. Using purposive sampling method, samples are obtained as much as 34 observations as much as 102 samples. The analysis technique used in this research is multiple linear regression and moderated regression analysis. The results showed the level of lending and third party funding positive effect on profitability, and credit quality weakens the influence of the loan portfolio on profitability. The higher the level of lending and placement in the form of credits, the higher profitability generated. The higher the level of problem loans LPD will reduce the rate of lending and reduced profitability.
Keywords: Profitability, Loan Portfolio, The Third Party Fund, Credit Quality